Facing the Facets: No Association Between Dispositional Mindfulness Facets and Positive Momentary Stress Responses During Active Stressors. (July 2021) - Saltsman, Thomas L.; Seery, Mark D.; Ward, Deborah E.; Radsvick, Tracy M.; Panlilio, Zaviera A.; Lamarche, Veronica M.; Kondrak, Cheryl L.
Mindfulness has been associated with enhanced coping with stress. However, it remains unclear how dispositional mindfulness impacts the nature and valence of experiences during active stressors. Across 1, 001 total participants, we used cardiovascular responses from the biopsychosocial model of challenge/threat to assess the degree to which individuals cared about a stressor in the moment and had a positive versus negative psychological experience. Although we found a small association between mindfulness—particularly the acting with awareness facet—and responses consistent with caring more about the stressor (i.e., greater task engagement), we found no evidence that mindfulness was associated with exhibiting a more positive psychological response (i.e., greater challenge) during the stressor. Despite no differences in the valence of momentary experiences as a function of mindfulness, individuals higher in mindfulness self-reported more positive experiences afterward. These findings suggest that dispositional mindfulness may benefit responses to active stressors only after they have passed.